Ischemic Mitral Regurgitation - Varma, Praveen Kerala (Ann Card Anaesth, 2017)
Ischemic mitral regurgitation (IMR) is a frequent complication of left ventricular (LV) global or regional pathological remodeling due to chronic coronary artery disease. It is not a valve disease but represents the valvular consequences of increased tethering forces and reduced closing forces. IMR is defined as mitral regurgitation caused by chronic changes of LV structure and function due to ischemic heart disease and it worsens the prognosis. In this review, we discuss on etiology, pathophysiology, and mechanisms of IMR, its classification, evaluation, and therapeutic corrective methods of IMR.